Relationship between self-esteem and suicidal ideation before and during COVID-19 in a non-clinical sample: mediating effects of psychological distress and hopelessness - Tan Dat, Nguyen; Mitsui, Nobuyuki; Asakura, Satoshi; Fujii, Yutaka; Toyoshima, Kuniyoshi; Kusumi, Ichiro (Frontiers in Psychiatry, 2023)
Several studies have highlighted the impact of the novel coronavirus disease (COVID-19) pandemic on suicide. Accordingly, investigating the risk factors of suicide during this crisis is important. Based on the escape theory of suicide, the current study examined the serial mediating roles of psychological distress and hopelessness in the relationship between self-esteem and suicidal ideation. It also aimed to explore whether or not the COVID-19 pandemic changed the mediation effect in any way. Data were collected from 645 university students before and during the pandemic. The study employed mediation and multi-group analyses to test the hypotheses. The results demonstrated that individuals with low self-esteem reported high psychological distress, which further lead to hopelessness and eventually heightened suicidal ideation. Multi-group analysis revealed that psychological distress exerted a greater impact on suicidal ideation during COVID-19. The finding suggested that self-esteem, hopelessness, and psychological distress could help elucidate the development of suicidal ideation. Clinicians may target these factors in suicide prevention programs, particularly in the settings of the COVID-19 pandemic or future crisis.